ANALISIS PENYAJIAN LAPORAN KEUANGAN PADA ORGANISASI SEKTOR PUBLIK DI BANDA ACEH (Studi Pada Pemerintah Aceh di Banda Aceh) - Indra Kesuma; Abad Abad (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2015)
Abstract: The purpose of this study was to examine the influence of human resource competencies, the role of internal auditor and controlling activity on the value of financial reporting information North Aceh regency government. The population in this study was all of the local working units (SKPD). Data used was primary data collected from respondents with questionnaire. Furthermore, for the data test done validity test, reliability test and hypothesis test. The getting data was done multiple linear regression. The result of this study showed that all variables are human resource competencies, the role of the internal auditor, and controlling activity simultaneously or partially have positive influence on value of financial reporting information.